2011
DOI: 10.1088/0004-637x/740/2/89
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Dependent Model for Magnetic Reconnection in the Presence of a Separator

Abstract: We present a model for separator reconnection due to an isolated reconnection process. Separator reconnection is a process which occurs in the neighborhood of a distinguished field line (the separator) connecting two null points of a magnetic field. It is, for example, important for the dynamics of magnetic flux at the dayside magnetopause and in the solar corona. We find that, above a certain threshold, such a reconnection process generates new separators, which leads to a complex system of magnetic flux tube… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…In a similar calculation to that detailed in Sect. 5 of Wilmot-Smith & Hornig (2011), it is possible to estimate the reconnection rate of our separator reconnection event; for the chosen parameters, this is approximately 8.85×10 7 V. These values agree well with the reconnection rates determined from numerical experiments of separator reconnection. As an example, the reconnection rate and lengthscales used in our study fall exactly within the range of rates and scales recovered from a dynamic flux emergence experiment studied in Parnell et al (2010b) which yielded multiple magnetic separators, strengthening our conclusion that the electric fields and reconnection event studied here reproduce behaviour which is expected to occur within the solar atmosphere.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In a similar calculation to that detailed in Sect. 5 of Wilmot-Smith & Hornig (2011), it is possible to estimate the reconnection rate of our separator reconnection event; for the chosen parameters, this is approximately 8.85×10 7 V. These values agree well with the reconnection rates determined from numerical experiments of separator reconnection. As an example, the reconnection rate and lengthscales used in our study fall exactly within the range of rates and scales recovered from a dynamic flux emergence experiment studied in Parnell et al (2010b) which yielded multiple magnetic separators, strengthening our conclusion that the electric fields and reconnection event studied here reproduce behaviour which is expected to occur within the solar atmosphere.…”
Section: Discussionsupporting
confidence: 77%
“…Our model can be broadly split into two parts: a (timedependent) large-scale electromagnetic field environment, into Wilmot-Smith & Hornig (2011). A black (white) sphere indicates the location of the upper (lower) null, the fan plane of which is seen in blue (orange) while the spines of both nulls are shown as thick black lines (due to the fan plane transparency, these lines adopt the colour of any fan planes they pass behind).…”
Section: Model Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…In 3-D, reconnection has been shown to occur at a multitude of sites, such as at topological features including 3-D null points (locations where all three components of the magnetic field equal zero) [e.g., Craig et al, 1995;Pontin et al, 2004Pontin et al, , 2005Pontin and Galsgaard, 2007;Priest and Pontin, 2009;Masson et al, 2009;Pontin et al, 2011] and magnetic separators (special field lines that link pairs of 3-D null points) [e.g., Priest and Titov, 1996;Longcope and Cowley, 1996;Longcope, 2001;Parnell et al, 2010aParnell et al, , 2010bWilmot-Smith and Hornig, 2011] or at the geometrical features known as quasi-separatrix layers (regions of magnetic field, which at one end are closely anchored but at the other end are anchored far apart) [e.g., Priest and Démoulin, 1995;Demoulin et al, 1996Demoulin et al, , 1997Aulanier et al, 2005Aulanier et al, , 2006 and in twisted or braided flux tubes [e.g., Galsgaard and Nordlund, 1996, 1997a, 1997bGalsgaard, 2006a, 2006b;Wilmot-Smith and De Moortel, 2007;Browning et al, 2008;Hood et al, 2009;Bareford et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…This also ties in nicely with the separator model of Wilmot-Smith and Hornig. 49 These authors developed a time dependent kinematic model for reconnection occurring along the separator joining two magnetic nulls. They found that singular (since in their model the field near the nulls is ideal) cyclic flows were driven at the nulls by reconnection along a single separator and that as the non-ideal region grows stronger multiple separators form.…”
Section: Discussionmentioning
confidence: 99%